SINERGI GERAKAN PEDULI LINGKUNGAN MELALUI KULIAH KERJA NYATA (KKN) DI DESA KEDUNG PENGAWAS KECAMATAN BABELAN KABUPATEN BEKASI - Desti Purnama; Yoan Dira Putri, Alya Wahyudi, Purwaningtyas, Novia Rachma Shinta, Indriani Agustiningsih, Vina Pusp (Adiba Aisha Amira, 2026)
Community service through Real Work Lectures (KKN) represents a concrete form of student contribution in addressing environmental and social problems as an implementation of the Tri Dharma of Higher Education. This activity was carried out by Group 74 of Universitas Bhayangkara Jakarta Raya at Kedung Pengawas Village, Babelan District, Bekasi Regency, under the theme